Knowing, doing and showing: a framework for evidencing education and learning designers’ practice in higher education - Jennifer Boreland; Tanya Henry; Sue Sharpe (Journal of Learning Development in Higher Education)
Much has been written about the diverse roles, responsibilities, and competencies of third space professionals working in education and learning design. While these debates are important, this paper begins with the premise that, regardless of title or exact role description, all designers are competent; they bring professional expertise to learning design which contributes to quality teaching and learning in their institutions.